Exploring development pathways for mining rural areas in the context of urban-rural integration: A case study in Shanxi Province, China. - Hao Xu; Shengyu Zhang; Zhenyu Wu (PLoS ONE)
In the process of urban-rural integration, rural depression poses a severe challenge to urban-rural coordination and regional sustainable development. Exploring development pathways for resource-dependent rural areas is an important measure to implement rural revitalization. Mining industry, shows beneficial in boosting the economies whiles brings ecological, physical/psychological and social problems to local community members. Therefore, efforts should be made to rural sustainable development in mining resource- dependent regions. Taking the traditional mining-industry Shanxi Province in North China as research case, this paper seeks to investigate the crucial factors influencing rural transformation development (RTD) of mining regions and explore development pathways for resource-dependent rural areas. First, rural economic-labor coupling mode and rural development type of 30 mining industries-based counties were determined based on the proposed rural economic-labor elasticity coefficient, followed by the hot spot analysis for understanding the spatial correlation of different coupling modes. Then, non-parametric test was applied for feature difference test. Finally, mining rural areas transformation pathways were given by using land use transfer matrix and chord diagram. Results indicated that the mean value and rank mean value of each indicator of different rural development types were basically consistent in the distribution form, while coupling modes showed a distinct difference. This research can provide important references for rural transformation promotion, rural revitalization and sustainable rural development of resource-dependent regions, especially for developing countries.